Comparative Predictors of Long-Term Success in Mesh-Based versus Tissue-Only Hernia Repair: A Meta-Analysis - Salman, Muhammad; Asmatullah; Rehman , Haseena; Khan Bangash, Rohail; Safiullah, Tahmeedah; Khan, Zarmina; Ibrahim Akhtar, Ibrahim Akhtar; Khan, Uzair; Saeed, Nadia (Indus Journal of Bioscience Research, 2024)
Introduction: Hernia repair ranks among the most commonly performed surgical procedures worldwide, with two predominant approaches: mesh-based and tissue-only techniques. Mesh repairs, while effective in reducing recurrence rates, are associated with complications like chronic pain and foreign body reactions. Conversely, tissue-only repairs avoid these complications but tend to have higher recurrence rates, particularly in complex hernias. This study aims to evaluate long-term predictors of success for both techniques to inform optimal surgical decision-making. Objective: To compare prognostic factors for mesh-based versus tissue-only hernia repair, emphasizing recurrence rates, complications, and patient-specific outcomes. Methods: A meta-analysis of randomized controlled trials and cohort studies published between 2000 and 2024 was conducted using PubMed, Scopus, Web of Science, and Cochrane databases. Studies with a minimum follow-up of one year were included. Data were analyzed using random effects models to evaluate recurrence, complications, and patient characteristics. Results: Mesh-based repairs demonstrated significantly lower recurrence rates, particularly in patients with large hernias or higher BMI. Lighter-weight meshes were associated with reduced chronic pain. Tissue-only repairs were more suitable for younger, slimmer patients with smaller hernias, demonstrating fewer complications but higher recurrence rates in complex cases. The findings underscore the importance of tailoring the surgical approach to patient-specific factors. Conclusion: The results highlight the need for individualized surgical strategies in hernia repair. Mesh-based techniques are recommended for complex cases due to their lower recurrence rates, while tissue-only repairs are more suitable for young, low-risk patients. These insights can guide clinicians in selecting the most appropriate repair technique, improving patient outcomes and satisfaction. By focusing on long-term predictors of success, this study provides a comprehensive evaluation of mesh-based and tissue-only hernia repairs, offering valuable guidance for patient-centered surgical decision-making.